Co-designing meaningful extended reality for physical rehabilitation: a stakeholder-driven approach to embodied telehealth - Elor, Aviv; Parrales, Adrian; Bourdon, Strauss Michael; Kuznetsov, Maxim; Callwood, Kamryn; Tu, Alyssa; Powell, Michael; Robbins, Ash; Bundle, Matthew; Skelton, Felicia; Touchett, Hilary (Frontiers in Virtual Reality, 2026)
IntroductionExtended Reality (XR) technologies offer unprecedented opportunities to redefine physical rehabilitation experiences through embodied telepresence and full-body motion tracking. Realizing meaningful XR in physical rehabilitation requires stakeholder input addressing remote embodied therapy's unique design challenges.MethodsThis study presents one of the first stakeholder co-design workshops on embodied telehealth for physical rehabilitation, engaging participants [N = 24 total including ten clinicians, eight patients, three designers, and three engineers] across five focus groups with stakeholders from clinical, academic, and industry settings. Through structured usability testing and a four-axis framework analysis, we evaluated immersive Virtual Reality (VR) applications supporting synchronous clinician-led embodied appointments and asynchronous clinician-authored patient home exercise programs with full-body tracked avatars and biomechanical assessments.ResultsStakeholder feedback reinforced the need for embodied agency with adaptive input modalities for diverse patient needs, ensuring clinical authenticity through real-time full-body tracking for accurate movement correction and scaling interaction complexity from minimal interfaces for VR novices (78% of participants) to customizable clinical dashboards. Crossstakeholder prioritization identified minimalist XR interface navigation (19 votes) and flexible clinical assessment capabilities (17 votes) as the highest-priority design requirements, while exit surveys suggested high patient comfort (M = 4.50/5) and strong clinician adoption interest (M = 4.14/5).DiscussionWe propose six design principles for meaningful XR telehealth in physical rehabilitation: 1) embodied guidance with real-time feedback, 2) progressive complexity with minimalist defaults, 3) adaptive accessibility through multi-modal input, 4) clinical authenticity via domain-specific assessments, 5) biomechanical precision for trust and safety, and 6) contextual onboarding to improve therapeutic competency. These findings offer design considerations for developing embodied XR telehealth systems that support sustained therapeutic engagement and meaningful rehabilitation outcomes.